Interceptive orthodontics for malaligned anteriors due to supplemental lateral incisor - Heena Sarangal; Ritu Namdev; Monika Rohilla (Wolters Kluwer Medknow Publications, 2020)
Supernumerary teeth are defined as the teeth that exceed the normal dentition, regardless of their morphology and location. They may closely resemble the teeth of the group to which it belongs, that is, molars, premolars, and anterior teeth. The most common complications associated are impaction, delayed eruption, crowding, and diastema. A case is presented where the diagnosis and extraction of the supplemental lateral incisor was done followed by 2 × 4 fixed orthodontic. Early intervention with 2 × 4 appliance is a potential treatment option for future, as it is a versatile, short-phase fixed appliance with clinical effectiveness and efficacy.